COP29: EAFF Call-to-action - Chevallier, Romy; Eastern Africa Farmers Federation (2024)
This document serves as a call-to-action from the Eastern Africa Farmers Federation (EAFF), representing 24 farmer organizations across 10 countries and over 25 million farmers. It urges global policymakers to amplify farmers' voices in climate policy discussions, particularly at COP29. The EAFF emphasizes the critical role of agriculture in combating climate change and advocates for increased financial and technical support to strengthen farmers' resilience to its impacts. The call highlights the need for equitable and inclusive climate solutions, focusing on key agenda items such as raising global ambition, setting new climate finance goals, addressing loss and damage, promoting agricultural adaptation, and enhancing soil health. Through this initiative, the EAFF aimed to influence policy, investment, and negotiations at COP29.